Step in Time: Conservation of Circadian Clock Genes in Animal Evolution. (7th September 2022) - Stanton, Daniel; Justin, Hannah S; Reitzel, Adam M
Abstract: Over the past few decades, the molecular mechanisms responsible for circadian phenotypes of animals have been studied in increasing detail in mammals, some insects, and other invertebrates. Particular circadian proteins and their interactions are shared across evolutionary distant animals, resulting in a hypothesis for the canonical circadian clock of animals. As the number of species for which the circadian clockwork has been described increases, the circadian clock in animals driving cyclical phenotypes becomes less similar. Our focus in this review is to develop and synthesize the current literature to better understand the antiquity and evolution of the animal circadian clockwork. Here, we provide an updated understanding of circadian clock evolution in animals, largely through the lens of conserved genes characterized in the circadian clock identified in bilaterian species. These comparisons reveal extensive variation within the likely composition of the core clock mechanism, including losses of many genes, and that the ancestral clock of animals does not equate to the bilaterian clock. Despite the loss of these core genes, these species retain circadian behaviors and physiology, suggesting novel clocks have evolved repeatedly. Additionally, we highlight highly conserved cellular processes (e.g., cell division, nutrition) that intersect with the circadian clock of some animals. The conservation of these processes throughout the animal tree remains essentially unknown, but understanding their role in the evolution and maintenance of the circadian clock will provide important areas for future study.